Disulfiram moderately restores impaired hepatic redox status of rats subchronically exposed to cadmium - Aida Begic; Ana Djuric; Milica Ninkovic; Ivana Stevanovic; Dragan Djurdjevic; Milos Pavlovic; Katarina Jelic; Ana Pantelic; Goran Zebic; Bratislav Dejanovic; Ivan Stanojevic; Danilo Vojvodic; et al. (Taylor & Francis Group, 2017)
Examination of cadmium (Cd) toxicity and disulfiram (DSF) effect on liver was focused on oxidative stress (OS), bioelements status, morphological and functional changes. Male Wistar rats were intraperitoneally treated with 1 mg CdCl2/kg BW/day; orally with 178.5 mg DSF/kg BW/day for 1, 3, 10 and 21 days; and co-exposed from 22nd to 42nd day. The co-exposure nearly restored previously suppressed total superoxide dismutase (SOD), catalase (CAT) and increased glutathione peroxidase (GPx) activities; increased previously reduced glutathione reductase (GR) and total glutathione-S-transferase (GST) activities; reduced previously increased superoxide anion radical (O2·−) and malondialdehyde (MDA) levels; increased zinc (Zn) and iron (Fe), and decreased copper (Cu) (yet above control value), while magnesium (Mg) was not affected; and decreased serum alanine aminotransferases (ALT) levels. Histopathological examination showed signs of inflammation process as previously demonstrated by exposure to Cd. Overall, we ascertained partial liver redox status improvement, compared with the formerly Cd-induced impact.